PENGARUH EFISIENSI DAN EFEKTIVITAS PAJAK HOTEL TERHADAPPENDAPATAN ASLI DAERAH KOTA BATAM - Jaya, Fernando Berrima; Nopiana, Puspita Rama (SCIENTIA JOURNAL, 2019)
This research aims to determine the effect of efficiency and the effectiveness of hotel tax on the original revenue of Batam city in 2012-2017. The population in this research uses the sampling census method in the form of reports on the original revenue of Batam city for 5 years with 60 months of data. The test result shows that the efficiency of the hotel tax has a positive and partially significant effect on the local revenue. Meanwhile, the test result on the effectiveness of hotel tax has a positive and partially significant effect on the local revenue. Simultaneously, the efficiency and the effectiveness of hotel tax have a positive and significant influence on the local revenue.